Real-time object control system using open source platform - Chang-Gyu Cgseong; Jung-Yee Kim; Doo-Jin Park (Institute of Advanced Engineering and Science, 2020)
Recently, the internet of things (IoT) has received great attention, and the demand for IOT applications in various fields is increasing. But drawbacks of IoT, such as having to use dedicated equipment and having to pay for a flat fee monthly, do not satisfy the consumers’ demands. These shortcomings of IoT is causing the appearance of users who try to design the environment of IoT that responds their demands and naturally, attempts to have monitoring system through open-source hardware like Arduino. Open source hardware has attracted a great deal of attention for the diffusion of the Internet of things as a key element of the Internet construction. The emergence of open source hardware, which has the advantage of low cost and easy and fast development, has made it possible to embody the idea of object Internet application services. In this paper, we design and implement a system that controls the objects in real time using open source hardware and MQTT protocol.